Carbapenem-resistant Gram-negative bacteria isolated from poultry samples: a cross-sectional study. (March 2019) - Elmanama, Abdelraouf A; Al-Reefi, Mariam R; Shamali, Madleen A; Hemaid, Haya I
Abstract: Background: Gram-negative bacteria are a common cause of human infections and can be transmitted through food handling and food consumption. Infection with carbapenemase-producing Gram-negative bacteria is becoming a worldwide threat, and is hard to cure because the broad-spectrum carbapenem antibiotics are considered a last resort for treatment. This research aimed to determine carbapenem resistance among Gram-negative bacteria from poultry samples. Methods: Samples from chicken litter, water, chicken feed, and intestinal content (220 samples in total) were collected during 2017 from representative slaughter houses, farms, and homes from four different randomly selected locations in the Gaza Strip. Samples were cultured and all isolates were identified using conventional techniques. The Clinical and Laboratory Standards Institute disk diffusion method was used to determine antimicrobial susceptibility to 15 antimicrobial agents. Carbapenemase was detected by the modified Hodge test. The multiple antibiotic resistance (MAR) index for each isolate was also calculated. Permission was obtained from the Ministry of Agriculture, and verbal consent was obtained from owners of the establishments. Findings: Escherichia species were the most frequently isolated bacteria (48 of 122; 39%), followed by non-lactose fermenting Enterobacteriacae (36 of 122; 30%) and other lactose fermenting Enterobacteriacae (32 of 122; 26%). The lowest frequency was for non-fermenting Gram-negative bacilli (six of 122; 5%). Most isolates were resistant to most antimicrobial agents tested except for meropenem and amikacin (3% were resistant to meropenem and amikacin), and 41 isolates (34%) were resistant to imipenem. From 122 tested isolates, 42 carbapenem-resistant isolates (36%) were detected. There was no significant difference in resistance to carbapenem or other drugs among isolates from the four locations. None of the three meropenem-resistant isolates and only five of the 41 imipenem-resistant isolates (12%) were positive for carbapenemase production. Most of the tested isolates (115 of 122 isolates; 94%) were resistant to five or more of the tested antimicrobials, and were regarded as multi-drug resistant according to MAR index results. Interpretation: Resistance to carbapenems as well as to other antimicrobials was high, as indicated by the MAR index. This might be due to the lack of regulation of the use of antimicrobials in poultry. The responsible authorities should take note of these findings and implement an immediate antimicrobial resistance monitoring programme for poultry. Cross-contamination prevention measures should also be promoted and implemented. Funding: None.